Tunisia : Request for an Extended Arrangement Under the Extended Fund Facility-Press Release; Staff Report; and Statement by the Executive Director for Tunisia. (IMF Staff Country Reports; Country Report ;, 2016)
This paper presents an overview of the macroeconomic condition of Tunisia. Tunisia has managed to preserve macroeconomic stability and initiate fiscal and banking reforms in a context marked by a prolonged political transition, spillovers from the crisis in Libya, and numerous exogenous shocks, including terror attacks. However, important vulnerabilities remain: economic activity is weak, employment is low, social tensions linger, spending composition has deteriorated, and external imbalances are high. To tackle these issues, Tunisia formulated a five-year (2016-20) economic vision in 2015, which is being developed into a detailed plan. The vision aims at promoting stronger and more inclusive growth in Tunisia.